The correlation between endoscopy manifestations and pathology outcome for diagnosis of celiac disease - Nikzamir, Mahfam; Nejad, Mohammad Rostami; Sadeghi, Amir; Moradi, Afshin; Mohaghegh, Hamid; Asadzadeh-Aghdaei, Hamid; Zali, Mohammad Reza (International journal of celiac disease, 2017)
Background: Celiac disease (CD) is one of the most common genetically based disease. Histological confirmation of the characteristic small bowel changes is currently considered the gold standard to establish diagnosis of CD in patients with positive antibody testing. The aim of this study is to determine the correlation between endoscopy manifestations and pathology outcome for diagnosis of CD. Materials & Methods: A total of 295 consecutive patients who were referred to our endoscopy section from March 2015 through March 2016 were enrolled into the study. All patients were underwent endoscopy, 4 biopsies were taken and their results were compared with pathology features. The relationship between age, sex, and pathology features and endoscopy manifestations were evaluated. Results: The mean age of the subjects was 46.7±15.5 years of which 147(49.8%) were female, and 148(50.2%) were male. No statistically significant correlation was showed between the age and gender with pathology features and endoscopy manifestations (p<0.05). Most patients with Marsh 1 and 2 had a normal endoscopy. CD was confirmed by serology in 3 cases (1%) with Marsh III. We did not observe significant correlation between endoscopy results and pathology features (P=0.674). Conclusions: Our data showed that endoscopy results are not specific for CD diagnosis, and biopsy should be collected in patients with suggested symptoms associated with the disease and regardless to endoscopic features.
Keywords: dospělí; Intestinal Mucosa; Celiac Disease; Middle Aged; lidé středního věku; lidé; Duodenum; Endoscopy, Gastrointestinal; Duodenoscopy; duodenum; Biopsy; Adult; celiakie; gastrointestinální endoskopie; střevní sliznice; duodenoskopie; biopsie; Humans